2019
DOI: 10.1007/s13300-019-0575-9
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Continuous Subcutaneous Insulin Infusion Versus Multiple Daily Injections in Patients with Poorly Controlled Type 2 Diabetes in Finland

Abstract: Introduction Although primarily utilized in type 1 diabetes, continuous subcutaneous insulin infusion (CSII) represents a useful treatment alternative for patients with type 2 diabetes who are unable to achieve good glycemic control despite optimization of multiple daily injections (MDI). The aim of the analysis reported here was to investigate the long-term cost-effectiveness of CSII versus MDI in type 2 diabetes patients with poor glycemic control in Finland. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Furthermore, 40 of the 118 subjects (33.8%) reported having either no significant change in frequency of hypoglyacaemic attacks or more hypoglycaemic attacks after CSII therapy. CSII has been highlighted in several health economic studies as being more cost effective than MDI, at least in adults [18,19], but not in children [20]. In the present study, the common issues encountered by the subjects regarding their medical devices should be reported to the Saudi Food and Drug Administration (SFDA) where approval of such devices takes place.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, 40 of the 118 subjects (33.8%) reported having either no significant change in frequency of hypoglyacaemic attacks or more hypoglycaemic attacks after CSII therapy. CSII has been highlighted in several health economic studies as being more cost effective than MDI, at least in adults [18,19], but not in children [20]. In the present study, the common issues encountered by the subjects regarding their medical devices should be reported to the Saudi Food and Drug Administration (SFDA) where approval of such devices takes place.…”
Section: Discussionmentioning
confidence: 97%
“…In the sensitivity analyses carried out in Finland, Literatura optimistic and pessimistic estimates were performed on a set of variables with an impact on investment return. The results suggested that CSII is more economical in patients with higher baseline HbA1c levels (ROZE et al, 2019). On the other hand, in the United Kingdom, the benefit of the use of CSII therapy is for those who have more than two glycemic severe events per year (17.4 events over eight years) and require hospital treatment at least once every eight months due to hypoglycemia symptoms (SCUFFHAM P and CARR L, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, CSII was associated with a gain in QALYs ranging between 0.17 and 0.43 compared with MDI. Furthermore, higher mean lifetime costs were estimated, but these costs were mitigated due to the reduction in short‐ and long‐term diabetes complications 61‐63 . Indeed, treatment costs in the CSII group were compensated by a 15% to 20% reduction in diabetes‐related complication costs.…”
Section: Insulin Pump Treatment In T2dmentioning
confidence: 99%